2015
DOI: 10.4012/dmj.2014-219
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of composite resins: A comparison among properties of commercial shades

Abstract: The aim of this study was to determine singular fluorescence qualities of different, commercially available resin composites shades. A total of 234 brand name colors including enamel, dentin and special shades were examined using a monochromator-based spectrophotometer. From the examined composites, Filtek TM Z250 (867±279) RFU and Supreme XT (dentin shades: (1,585±507) RFU; enamel shades: (4,473±330) RFU) are the only brands with a mean fluorescence maximum that resembles the fluorescence of natural samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 21 publications
5
53
1
1
Order By: Relevance
“…However, which fluorescence scale do the manufacturers follow? It seems that CRs are more or less fluorescent according to different manufacturers, 7,8 corroborating the results of this study. Moreover, FI seems to be not related to shade or the characteristics of the resin particles.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, which fluorescence scale do the manufacturers follow? It seems that CRs are more or less fluorescent according to different manufacturers, 7,8 corroborating the results of this study. Moreover, FI seems to be not related to shade or the characteristics of the resin particles.…”
Section: Discussionsupporting
confidence: 80%
“…The results showed that the CR Filtek Z350 obtained FI means closest to those of tooth, corroborating previous studies. 8,23 Esthet-X, Amelogen Plus, and Durafill VS showed higher intensity values than those of tooth, as observed by da Silva et al 23 It may be related to differences in fluorophore within the composition of each CR, trade secret not disclosed by the manufacturers. The differences in fluorescence values could be related to the difference in type of particles as well as resin matrix.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations